Assessment of effect of management practices and agro-ecology on water productivity of major crops in Meja Watershed, Jeldu District, Oromia Region, Ethiopia - Asfaw, A. (Ambo University, 2012)
Low water use efficiency is a challenge to crop production in Sub-Sahara African countries. Water is getting continuously scarce due to increased demand and shrinking availability induced mainly by climate change. As agriculture is the major consumer of water, improving crop water productivity is among the ways of overcoming the challenge. Crop production under rainfed system is the major livelihood strategy for smallholder farmers in Ethiopia. The major objective of this study is, therefore, to estimate water productivity of major crops grown under rainfed system in Meja watershed as influenced by management practices and local agro-ecology. The research work mainly depends upon house hold survey and field measurement conducted from July 2011 to February 2012. Agronomic practices used for major crops were monitored on randomly selected farmers’ fields, and biomass and grain yield were determined at harvest. Crop water requirement was simulated by CROPWAT model from which the average consumptive water use (m3) by each crop was calculated. In a mixed crop livestock farming system, farmers obtain benefit not only from grain but also from straw (primarily as animal feed). In line with this demand, the average biomass water productivity magnitudes for barley (Hordeum vulgare), wheat (Triticum Vulgare), teff (Eragrostis tef), sorghum (Sorghum bicolor), potato (Solanum tuberosum) and maize (Zea mays) were found to be 3.57, 4.82, 2.31, 6.45, 14.61 and 6.68kg/m3, respectively while the corresponding grain water productivity were 1.32, 1.42, 0.65, 0.98, 14.25 and 1.42kg/m3 in that order. Based on the local market values of the crops’ biomass, economic water productivity of barley, wheat, teff, sorghum, potato and maize were determined to be 10.09, 10.84, 8.45, 8.05, 28.82 and 10.18 Birr/m3, respectively. The mean biomass water productivity showed significant variation across the three local agro-ecological zones due to variations in seeding rate, tillage frequency, fertilizer rates and other agronomic practices. Hence, farmers can enhance economic benefit from the land and water resources they are endowed with rainfed by using improved technologies that could enhance grain and biomass yield. Moreover, implementation of integrated crop-soil-water management strategy is crucial to bring sustainable agricultural production and ensure food security in the long run. The correlation test between some management practices and major crops water productivity also indicated no significance but tended to correlate indicating a need to have detailed further study.